2010
DOI: 10.1111/j.1442-2042.2010.02666.x
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset incontinence in a cohort of radical prostatectomy patients

Abstract: A cohort of 235 subjects, who underwent radical prostatectomy from 1994 to 2002, completely continent at the 2-year follow up and with the last follow-up visit in 2009, was examined to assess incidence and risk factors of late-onset incontinence. Median follow up was 100 months, range 84-176. At the last follow-up visit, 209 (89%) maintained continence, and 26 (11%) became incontinent. Specifically 14 out of 26 (6%) used one pad and 12 (5%) used two or more pads daily. Incidence of age Ն65 years at radical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In our series, however, the mean urinary function score and continence rate beyond 5 years appeared to be stable. A previous retrospective study showed that late incontinence occurred in more than 10% of patients at 7 or more years after undergoing RP . Given the small subset of evaluable patients on which the results are based, these results might limit the generalizability of our conclusion.…”
Section: Discussionmentioning
confidence: 81%
“…In our series, however, the mean urinary function score and continence rate beyond 5 years appeared to be stable. A previous retrospective study showed that late incontinence occurred in more than 10% of patients at 7 or more years after undergoing RP . Given the small subset of evaluable patients on which the results are based, these results might limit the generalizability of our conclusion.…”
Section: Discussionmentioning
confidence: 81%
“…Similar findings have been obtained at 15 years after surgery [ 16 ]. Naselli et al found that 11% of patients with complete continence after 2 years later developed urinary incontinence [ 17 ]. In the current study, age was an independent factor related to urinary function and bother, and the worsening of these functions in the third year after surgery is similar to that observed in the reports above.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic floor muscle training is a common practice after RARP as it improves pelvic muscle strength and continence occurs faster when adopted [ 8 ]. As ageing is associated with late onset incontinence following radical prostatectomy, one should be counselled for the same [ 9 ].…”
Section: Introductionmentioning
confidence: 99%